2018
DOI: 10.26650/fnjn387185
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breathing Exercises on Preventing Postoperative Atelectasis: A Randomized Controlled Trial

Abstract: Aim: This study aims to assess the effect of pre-operative breathing exercises provided to patients undergoing open-heart operation on atelectasis development during the post-operative period. Method: This randomized controlled study was conducted with 48 patients hospitalized for open-heart surgery. Training was provided to the patients in the experimental group in the form of breathing exercises and spirometry and the instructed exercises were performed by the patients for 7 days before the operation. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In current study, the elderly patients in intervention group had significantly improved oxygen saturation compared to the control group, that in concordance with the results of Gbiri et al (26) , Devecel et al (27) and Svensson-Raskh et al (28) . High saturation results could be seen as yet another benefit and a sign of the success of preoperative instruction.…”
Section: Discussionsupporting
confidence: 92%
“…In current study, the elderly patients in intervention group had significantly improved oxygen saturation compared to the control group, that in concordance with the results of Gbiri et al (26) , Devecel et al (27) and Svensson-Raskh et al (28) . High saturation results could be seen as yet another benefit and a sign of the success of preoperative instruction.…”
Section: Discussionsupporting
confidence: 92%
“…The characteristics of the included studies by type of intervention, aggregate data from the included studies by type of intervention, RoB assessment, summary of findings, excluded studies, studies that fit the inclusion criteria but had no usable data, and relevant protocols of ongoing or unpublished studies are shown in the online supplemental digital content. We identified eight types of interventions administered in the preoperative period: nutritional (51 studies),30–80 respiratory (30 interventions of 29 studies)81–109 exercise (27 studies),110–136 multimodal (25 studies),100 108 137–159 educational (17 studies),160–176 psychological (16 studies),177–192 smoking and alcohol cessation (7 studies)193–199 and pharmacological (5 studies)200–204 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional interventions were further subdivided into standard oral nutritional supplements (ONS, 7 studies),30–35 69 oral immunonutrition supplements (19 studies)36–47 70–75 80 weight loss interventions (11 studies),48–51 53–57 76 205 oral prebiotics and probiotics (6 studies),58–61 77 78 dietary optimisation of comorbidities (3 studies)62–64 and other (5 studies, generally including administration of nutritional supplements such as fish oils, antioxidants, etc) 65–68 79. Respiratory interventions were further subdivided into IMT (18 studies),81–95 106 108 109 IS (5 studies)90 96–99 and combined respiratory interventions (7 studies, involving combinations of IMT, IS, other respiratory exercises and physical exercises) 100–105 107…”
Section: Resultsmentioning
confidence: 99%
“…Pneumothorax can occur spontaneously or secondary to surgery. The incidence of pneumothorax is quite high, based on an epidemiological study from 2011-2015 there were 10,500 cases in Germany due to pneumothorax [14].…”
Section: Pneumothoraxmentioning
confidence: 99%
“…Several surgical or medical procedures can lead to intra-or post-surgical pneumothorax. Acupuncture, orthopedic injections, CT scan-guided lung biopsy, bronchoscopy, central venous catheter (CVC) insertion, or thoracocentesis may cause damage to the pleura visceralis and respiratory air to enter the pleural cleft, resulting in a pneumothorax [14].…”
Section: Pneumothoraxmentioning
confidence: 99%